The role of apoptosis during infection of Aedes aegypti by Sindbis virus. - Wang, Hua (Kansas State University, 2011)
Each year, over 500 million people are infected with mosquito-borne diseases, including malaria, yellow fever and dengue fever, which cause several million deaths, and long-term disability and suffering. This dissertation focused on the mosquito Aedes aegypti, a vector for dengue virus and yellow fever virus. Since Sindbis virus (SINV) is an arthropod-borne virus (arbovirus) that is vectored by A. aegypti and is well characterized at the molecular level, the SINV - A. aegypti model was used to determine whether apoptosis plays a role in the control of vector competency. In Chapter 2, the effects of inducing or inhibiting apoptosis on SINV replication were tested in mosquito cells. It was observed that recombinant SINVs expressing pro-apoptotic genes caused extensive apoptosis in mosquito cells, with decreased virus production after the cells underwent apoptosis. Infection of mosquito cells with SINV expressing the caspase inhibitor P35 inhibited actinomycin D-induced apoptosis, but had no observable effects on virus replication. This study was the first to test directly whether inducing or inhibiting apoptosis affects arbovirus replication in mosquito cells. Chapter 3 examined the effects of silencing apoptosis regulatory genes on SINV replication and dissemination in A. aegypti. Genes which either positively or negatively regulate apoptosis were silenced by RNA interference in mosquitoes, which were then infected with a recombinant SINV expressing green fluorescent protein (GFP). Reciprocal effects were observed on both the occurrence and intensity of expression of GFP in various tissues. These results suggest that systemic apoptosis positively influences SINV replication in A. aegypti. This was the first direct study to explore the role of apoptosis in determining mosquito vector competence for arboviruses. Finally, in Chapter 4, the mechanisms of apoptosis were explored in A. aegypti. Overexpression of IAP antagonists caused extensive cell death in mosquito cells, while silencing the expression of IAP antagonists attenuated apoptosis. The results showed that the IAP binding motif (IBM) of IAP antagonists was critical for their binding to AeIAP1. The IAP antagonists released initiator and effector caspases from AeIAP1 by competing for the binding sites and caused caspase-dependent apoptosis. These findings imply that the mechanisms of IAP antagonists regulating apoptosis are conserved between mosquitoes and the model insect where apoptosis has been mainly studied, Drosophila melanogaster.
Keywords: Apoptosis; Vector biology; Arboviruses; Medical entomology; Mosquitoes; Biochemistry (0487); Entomology (0353); Virology (0720)